2000
DOI: 10.1128/iai.68.1.30-37.2000
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Periplasmic Cu,Zn Superoxide Dismutase Enhances Survival of Escherichia coli Invasive Strains within Nonphagocytic Cells

Abstract: We have studied the influence of periplasmic Cu,Zn superoxide dismutase on the intracellular survival of Escherichia coli strains able to invade epithelial cells by the expression of the inv gene from Yersinia pseudotuberculosis but unable to multiply intracellularly. Intracellular viability assays, confirmed by electron microscopy observations, showed that invasive strains of E. coli engineered to increase Cu,Zn superoxide dismutase production are much more resistant to intracellular killing than strains cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 47 publications
5
47
1
Order By: Relevance
“…With two functional sodC genes, S. choleraesuis achieves enhanced survival under the conditions of oxidative stress encountered during experimental murine infection by the oral or parenteral route, reproduced ex vivo in experimental infection of activated macrophages. This observation finds a correlate in the observations of Battistoni et al (2000). An E. coli strain engineered to increase [Cu,Zn]-SOD production was found to be much more resistant to intracellular killing than the wild-type strain, while there was very little difference in survival between the wild-type and a sodCnull mutant.…”
Section: Discussionsupporting
confidence: 60%
“…With two functional sodC genes, S. choleraesuis achieves enhanced survival under the conditions of oxidative stress encountered during experimental murine infection by the oral or parenteral route, reproduced ex vivo in experimental infection of activated macrophages. This observation finds a correlate in the observations of Battistoni et al (2000). An E. coli strain engineered to increase [Cu,Zn]-SOD production was found to be much more resistant to intracellular killing than the wild-type strain, while there was very little difference in survival between the wild-type and a sodCnull mutant.…”
Section: Discussionsupporting
confidence: 60%
“…2). In fact, 24 h after the infection nearly all E. coli HB 101 (pRI203) cells appeared damaged within the endosome-lysosome ( Fig.2A), as already described (17). On the contrary, at the same time post-infection, most of the E. coli HB 101(pRI203) cells observed within HeLa cells treated with DPI were still intact (Fig.…”
Section: Effect Ofnadph Oxidase Inhibitors On Bacterial Intracellularsupporting
confidence: 74%
“…Production of oxygen radicals might be involved in the response to bacterial invasion either by inducing cytokine production or by inducing oxidative damage to intracellular bacteria. This latter possibility is supported by the observation that phagocytic stimuli induce superoxide release by epithelial cell (22) and by our recent demonstration that increased expression of the sodC gene enhances survival of invasive E. coli strains within HeLa and Caco-2 cells (17). These two cell lines express homologs of gp91phox, the catalytic subunit of the phagocytic NADPH oxidase (23).…”
Section: Effect Ofnadph Oxidase Inhibitors On Bacterial Intracellularsupporting
confidence: 62%
“…Previous studies in cultured macrophages (11) and mice (8,9,16,18,21,23,24) have shown a consistent contribution of SodCI to Salmonella virulence. However, some of these studies have found a substantial role of SodCII in virulence as well (8,12,16,18), whereas others have not (21,23,24).…”
Section: Discussionmentioning
confidence: 99%